Cystemno and informational efficiency analysis scales Qualimetry academic obdaro-vanosti - Камишин, В. В. (Problems of Informatization and Control, 2013)
Given the importance of providing clear Qualimetry academic talent and application-sovuyuchy methods of system analysis, comparative analysis of the most prominent knowledge assessment (4-point, 7-point (ECTS), stenayniv 9-point, 10-point walls, 100-point and 200 -point) according to the criteria of nominal and quantitative-qualitative distinction learners